Tautology and Pleonasm in Political Interviews: A Semantic study (Journal of the College of Languages (JCL), 2024)
Pleonasm refers to the involvement of unnecessary words or morphemes represents pleonastic words which repeat a mentioned information elsewhere, whereas tautology refers to the inacceptable repetition of the same ideas, words, or phrases by using diverse words. In English, there is a perplexity to distinguish some elements that may be misled to be regarded as pleonastic or tautological. The current study aims at analysing two political interviews in the light of pleonasm and tautology concepts and find out the differences between them semantically. The data analysis is taken from two presidential interviews for the American presidents Trump and Biden in 2020. The study has concluded that tautology and pleonasm can be used in disparate degrees in political speeches. Using tautology is more necessary than pleonasm in political speeches, in which pleonasm concentrates on ideas and implied meaning, which can be misled to simple, ordinary people, while tautology is clear and can be understood by any simple brain in spite that it is dull and boring sometimes if the repetition is exaggerated, but can be perceived easily to focus on some important ideas the politician sees it is significant.